Double parton interactions in γ+3 jet events in pp̄ collisions at √s=1.96TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; et al. (American Physical Society (APS), 2010)
We have used a sample of γ+3 jets events collected by the D0 experiment with an integrated luminosity of about 1fb-1 to determine the fraction of events with double parton scattering (fDP) in a single pp̄ collision at √s=1.96TeV. The DP fraction and effective cross section (σeff), a process-independent scale parameter related to the parton density inside the nucleon, are measured in three intervals of the second (ordered in pT) jet transverse momentum pTjet2 within the range 15≤pTjet2≤30GeV. In this range, fDP varies between 0.23≤fDP≤0.47, while σeff has the average value σeffave=16.4±0.3(stat) ±2.3(syst)mb. © 2010 The American Physical Society.